Optical Metamaterials: Qualitative Models Introduction to Nano-Optics and Optical Metamaterials - Chipouline, Arkadi (Springer Series in Optical Sciences,, 2018)
This textbook bridges the gap between university courses on electrodynamics and the knowledge needed to successfully address the problem of electrodynamics of metamaterials. It appeals to both experimentalists and theoreticians who are interested in the physical basics of metamaterials and plasmonics. Focusing on qualitative fundamental treatment as opposed to quantitative numerical treatment, it covers the phenomena of artificial magnetization at high frequencies, and discusses homogenization procedures and the basics of quantum dynamics in detail. By considering different phenomena it creates a self-consistent qualitative picture to explain most observable phenomena. This allows readers to develop a better understanding of the concepts, and helps to create a conceptual approach, which is especially important in educational contexts. This clearly written book includes problems and solutions for each chapter, which can be used for seminars and homework, as well as qualitative models that are helpful to students. .